Removal of Benzene and Toluene from their Polluted Aqueous solutions by using Natural Adsorbent - Rauof, Abdul Latif Mohammed; Hammud, Kafa Khalaf; Mohammed, Jassim Mahdi; Akosh, Nibras Abdul Hussain; Hamza, Faehaa Mseer; Hassan, Mustafa Salah; Omran, Nasir Mohammed; Zanad, Duraid Essa; Ammen, Eman Wageh (Journal of Petroleum Research and Studies, 2017)
Low cost activated carbon was produced from available consumed black tea with microwave technique and employed as an effective adsorbent for removal of benzene (Bz) and toluene (T) from water. The resulted activated carbon was characterized by utilizing dye (methylene blue (MB) and methyl violet (MV)) adsorption procedures and several techniques such as Fourier transform Infrared (FTIR), scanning electron microscopy (SEM), X-Rays diffraction (XRD). Commercial activated carbon and filter sand as individual and blend samples were also subjected to adsorption of MB, MV, Bz, and T. All obtained results were tabulated and discussed after qualitative and quantitative determinations by applying ultraviolet- visible spectroscopy (UV-VIS) for MB and MV dyes, and gas chromatography (GC) instrumentations for Bz and T.